Development of a Web-Based Internship Registration System to Improve Administrative Efficiency - Hany Nur Apriyanti; Ika Nova Briyanti; Zainul Hakim; Suparman (Komunitas Dosen Indonesia, 2025)
The rapid advancement of information technology in the era of globalization has significantly impacted sectors such as communication, education, economy, and culture. Information is now easily accessible, overcoming traditional barriers of distance and time. In computer science, computers have become essential tools for meeting information needs in personal, educational, business, and governmental settings due to their ability to process data rapidly and accurately. In education, particularly in vocational schools, there is a need for an information system to streamline access to data, especially related to internship (PKL) activities. This research focuses on developing a web-based internship registration system at SMK Persada Pasarkemis to address issues like document loss, delays in data entry, and errors in manual processes. The system aims to improve registration efficiency by allowing users to upload documents, track registration status in real-time, and enhance transparency and data access for teachers. This study seeks to implement a computer-based system that optimizes PKL data management, reducing administrative bottlenecks and ensuring accurate data processing. The expected outcome is a more organized and efficient PKL registration process. Future developments include integrating the system with other information systems and adding features based on user feedback. The software development process follows the Software Development Life Cycle (SDLC) using the Waterfall model, chosen for its structured, sequential approach. This methodology ensures that each phase design, requirements analysis, testing, implementation, and maintenance is thoroughly completed before moving to the next, ensuring a reliable, well-documented system that meets user needs.